Electrochemical evaluation of the stability and capacity of r-GO-wrapped copper antimony chalcogenide anode for Li-ion battery - Yadav, Poonam; Sharma, Neha; Patrike, Apurva; Sabri, Ylias M.; Jones, Lathe A.; Shelke, V. Manjusha (ChemElectroChem, 2020)
Poor cycling stability and capacity fade are primary concerns for next-generation anode materials for Li-ion batteries. In non-carbonaceous anode materials, alloying with Li leads to volume increase that affects practical applications, and increase in particle size, amorphization and reduced conductivity can all lead to a loss of performance. In this work, binary antimony sulfide (Sb2S3) and ternary copper antimony sulfide (CuSbS2) are synthesized by a convenient solvothermal process. These materials are used to study the Li-active/inactive concept, by incorporating Cu into Sb(2)S(3)forming CuSbS(2)wherein Cu is Li inactive whereas Sb is Li active. By direct comparison, we have shown that incorporating Cu into binary antimony sulfide (Sb2S3) resulting into ternary copper antimony sulfide (CuSbS2) addresses the problem of poor conductivity and capacity loss, as Cu provides conductivity leading to enhanced charge transfer and prevents Sb particle aggregation while charge-discharge by exhibiting spectator or diluent ion effect. The better performance of CuSbS(2)is associated with the better Li(+)ion diffusion in the CuSbS2(D=8.97x10(-15) cm(2) s(-1)) compared to Sb2S3(D=2.76x10(-15) cm(2) s(-1)) and lower series resistance of CuSbS2(R=4.70x10(5) omega) compared to Sb2S3(R=5.81x10(8) omega). We have also investigated the composite with the addition of rGO. The CuSbS2-rGO delivered a reversible capacity of 672 mAh g(-1)after 1000 cycles at 200 mA g(-1)which has shown best performance.
Keywords: Batteries; chalcogenides; Diffusion coefficient; lithium; Ternary sulfides

Ice-colloidal templated carbon host for highly efficient, dendrite free Li metal anode - Patrike, Apurva; Kaniyamparambil, Karthika; Wahid, Malik; Chaturvedi, Vikash; Shelke, Manjusha (Carbon, 2021)
With its high theoretical specific capacity value, lithium metal itself would be an ideal anode material for rechargeable Li-ion batteries (LIBs). However, practical application of lithium metal is obstructed due to lithium dendrite growth during cycling leads to unstable SEI formation, volume fluctuation and safety hazard. Herein, we have developed a novel high surface area carbon network with both meso (∼20 nm) and micron (∼1–2 μm) size porosity, via ice-colloidal templating, as a scaffold for stable lithium metal anode mitigating lithium dendrite formation. The 3D porous nitrogen doped carbon (3D PNC) network is capable of lithium deposition equivalent to 10 mAhcm−2 at 2 mAcm−2 current density with 99.96% coulombic efficiency for 100 cycles. Moreover, 3D PNC when subjected to 3000 h of continuous plating-stripping measurements (∼700 cycles) depicts the coulombic efficiency of 99.84% with no observable dendrite growth at the current density of 2 mAcm−2 and lithium intake capacity of 5 mAhcm−2. A full cell of lithium plated 3D PNC anode with LiFePO4 shows an excellently stable performance up to 50 cycles at an input current density of 50 mAg−1, with a coulombic efficiency retention of 99.73%.

Laser patterning of boron carbon nitride electrodes for flexible micro-supercapacitor with remarkable electrochemical stability/capacity - Karbhal, Indrapal; Basu, Aniruddha; Patrike, Apurva; Shelke, Manjusha V. (Carbon, 2021)
High performance, all solid-state planar micro-supercapacitor (MSC) with interdigitated Boron carbon Nitride (BCN) electrodes are fabricated via fast, scalable laser patterning technique. Heteroatom doping desirably enhances the electrochemical activity of carbon electrodes. This BCN based micro-supercapacitor showed comparatively very high specific capacitance of 72 mFcm(-2) at a current density of 0.15 mAcm(-2). Even at a high current density of 1 mAcm(-2) device showed specific capacitance as high as 17 mFcm(-2). It has demonstrated excellent electrochemical stability when tested up to 80000 cycles without any sign of further decay in capacity/efficiency. This device showed stable capacity even after bending at 150 degrees angle, for 1500 times during cycling showing remarkable flexibility. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: BCN; Co-doping; Energy storage; Flexible; Laser patterning; Micro-supercapacitor

Honeycomb boron carbon nitride as high-performance anode material for li-ion batteries - Karbhal, Indrapal; Chaturvedi, Vikash; Patrike, Apurva; Yadav, Poonam; Shelke, V, Manjusha (ChemNanoMat, 2022)
3D Porous carbon-based materials are well known for their excellent mechanical and electrochemical properties for various energy storage applications including Li-ion Battery (LIB) anodes. However, their commercial application is limited due to their low theoretical specific capacity. Heteroatom doping in carbonaceous networks proved an efficient way to modify the surface properties, which considerably improves the Li intake capacity and Li diffusion in porous carbon materials. In this work, we have synthesized 3D honeycomb boron carbon nitride (HBCN) from boric acid, glucose, and cyanamide. Silica nanoparticles (SiO2 NPs) are used as structure-directing agents to replicate well-organized honeycomb structures. HBCN possesses a high specific surface area (SSA) of similar to 597 m(2) g(-1), with a uniform porosity distribution, low charge transfer resistance, and steady Li flux. When analyzed as an anode material for LIB, HBCN demonstrated an excellent specific capacity of similar to 652 mAhg(-1) and 408 mAhg(-1) at an input current density of 100 mAg(-1) and 1 Ag-1 respectively and an energy density of 227 Wh kg(-1) at 1 C rate in a full cell LIB. These results indicate that the doping of B and N hetero atoms is significantly advantageous for LIBs application.
Keywords: 3D-Architecture; Heteroatom Doping; High-Performance Anode; Honeycomb boron carbon nitride (HBCN); Li-ion battery

Research progress and perspective on lithium/sodium metal anodes for next-generation rechargeable batteries - Patrike, Apurva; Yadav, Poonam; Shelke, Vilas; Shelke, Manjusha (ChemSusChem, 2022)
With the development of consumer electronic devices and electric vehicles, lithium-ion batteries (LIBs) are vital components for high energy storage with great impact on our modern life. However, LIBs still cannot meet all the essential demands of rapidly growing new industries. In pursuance of higher energy requirement, metal batteries (MBs) are the next-generation high-energy-density devices. Li/Na metals are considered as an ideal anode for high-energy batteries due to extremely high theoretical specific capacity (3860 and 1165 mAh g(-1) for Li and Na, respectively) and low electrochemical potential (-3.04 V for Li and -2.71 V for Na vs. standard hydrogen electrode). Unfortunately, uncontrolled dendrite growth, high reactivity, and infinite volume change induce severe safety concerns and poor cycle efficiency during their application. Consequently, MBs are far from commercialization stage. This Review represents a comprehensive overview of failure mechanism of lithium/sodium metal anode and its progress for rechargeable batteries through (i) electrolyte optimization, (ii) artificial solid-electrolyte interphase (SEI) layer formation, and (iii) nanoengineering at materials level in current collector, anode, and host. The challenges in current MBs research and potential applications of lithium/sodium metal anodes are also outlined and summarized.
Keywords: anode; Batteries; dendrite growth; Electrolytes; Energy storage

Few-layer graphene lithiophilic and sodiophilic diffusion layer on porous stainless steel as lithium and sodium metal anodes - Patrike, Apurva; Wasnik, Kundan; Shelke, Manjusha V. (Chemistry-An Asian Journal, 2023)
In order to subdue the obvious problem of uneven electric field distribution on regularly used copper/aluminum current collectors for alkali metal batteries, graphene on porous stainless steel (pSS_Gr) was fabricated using the ion etching technique that is employed as an effective host for lithium and sodium metal anodes. The binder-free pSS_Gr demonstrated stable Li plating and stripping at areal current and capacity of 6 mA cm(-2) and 2.54 mAh cm(-2), respectively, for over 1000 cycles with 98% coulombic efficiency (C.E.). Also, in the case of Na metal anode, the host has shown stable performance at 4 mA cm(-2) and 1 mAh cm(-2) over 1000 cycles with similar to 100% C.E.. Further, a full cell composed of Li-plated pSS_Gr as an anode and LiFePO4 as a cathode is electrochemically tested at 50 mA g(-1) current density with stable 100 cycles.
Keywords: Few layer graphene; Free-standing; Li and Na metal functional host; Na depth profiles; post-cycling XPS

High rate, high temperature, dendrite free plating/stripping of Li in 3-dimensional honeycomb boron carbon nitride to realize an ultrastable lithium metal anode - Patrike, Apurva; Karbhal, Indrapal; Wasnik, Kundan; Torris, Arun; Maibam, Ashakiran; Krishnamurty, Sailaja; Shelke, V, Manjusha (Journal of Energy Storage, 2023)
Lithium (Li) metal could be the anode of choice for energy dense Li-batteries owing to its high theoretical specific capacity. However, low coulombic efficiency and poor safety on account of the occurrence of the Li-dendrites during charging-discharging pose a bottleneck for practical applications. In this work, we report a high-rate plating and stripping of Li through host engineering to realize ultrastable Li metal anode (LMA). Benchmark plating/stripping efficiency could be achieved via uniquely structured, highly ordered honeycomb boron carbon nitride (HBCN) as a functional scaffold. Boron and nitrogen doping, large surface area and ordered mesoporous structure induce homogeneous solid electrolyte interface (SEI) layer formation and provide numerous nucleation sites with subsequent dendrite-free growth with 99.98 % coulombic efficiency at 8 mA cm(-2) high current and 10 mAh cm(-2) capacity over 3000 cycles. Via post-cycling advanced characterizations techniques of Ex-situ XPS, 3D X-ray micro-tomography analyses and FESEM, we demonstrate the formation of a stable SEI layer and morphological changes that occurred during Li plating cycles in the HBCN structure. Computational studies validate the high lithium plating-stripping efficacy of HBCN to its highly ordered porous nature, exothermic Li-binding and upshift in the Fermi levels. When tested at elevated temperature (50 degrees C), a stable Li plating-stripping in HBCN is realised at 4 mA cm(-2) current and 10 mAh cm(-2) capacity values with similar to 100 % C.E. Furthermore, we report the results of testing a Li metal cell comprised of Li deposited HBCN anode and LiFePO4 (LFP) cathode.
Keywords: Boron carbon nitride; Dendrite-free Li metal anode; Functional scaffold; High temperature plating/stripping of Li; Molecular planarity parameter; X-ray micro-tomography

Template directed synthesis of boron carbon nitride nanotubes (BCN-NTs) and their evaluation for energy storage properties - Karbhal, Indrapal; Chaturvedi, Vikash; Yadav, Poonam; Patrike, Apurva; Shelke, Manjusha V. (Advanced Materials Interfaces, 2023)
A unique approach has been applied for the synthesis of 1D boron carbon nitride nanotubes (BCN-NTs) using MnO2 nanowires as templates. BCN-NTs have been evaluated in Na-ion batteries, Li-ion batteries, and supercapacitors as electrode material and exhibited excellent and stable electrochemical performance. BCN-NTs as an anode for Na-ion battery has been shown to be highly stable up to 3000 cycles with capacity retention of 95 mAh g(-1), at a high current density of 1 A g(-1). In the case of the Li-ion battery, these BCN-NTs show a specific capacity of 563 mAh g(-1) at a current density of 50 mA g(-1). Finally, when used as an electrode for a supercapacitor, BCN-NTs display a specific capacity of 221 F g(-1) at a current density of 3 A g(-1) and 168 F g(-1) even at a very high current density of 30 A g(-1) exemplifying the excellent rate performance. The multifunctionality and stable performance of BCN-NTs among various electrochemical energy storage systems highlight the robustness of the material and make it an excellent candidate for scalable production and commercialization.
Keywords: 1D-nanostructure; boron carbon nitride nanotubes (BCN-NTs); Co-doping; Li-ion battery; Na-ion battery; Supercapacitors

Ti3C2Tx-Nb2Mo3O14 composite as novel anode to realize high power density combined with high stability in a hybrid lithium-ion capacitor - Pawar, Meenakshi D.; Thripuranthaka, Marulasiddappa; Patrike, Apurva; Deshmukh, Ashvini B.; Chaturvedi, Vikash; Krishnan, Arun; Shivade, Rajkiran; Shelke, Manjusha V. (Energy Technology, 2023)
Lithium-ion capacitors (LICs), with their higher energy density at high power capability, stand out as the future generation of energy-storage devices. Herein, the nanocomposite of Ti3C2Tx MXene with Nb2Mo3O14 is prepared by a one-step hydrothermal method and studied as an electrode material for LIC. The asfabricated composite MXene niobium molybdenum oxide (MXNMO) achieves a high reversible capacity of 205 mAh g(-1) at 100 mA g(-1) current density with outstanding cyclability. Further, asymmetric LIC full-cell device composed of MXNMO anode with supercapacitor grade activated carbon as a cathode delivers an energy density of 37.8 Wh kg(-1) (0.25 A g(-1)) and a higher power density of 4244 W kg(-1) (5 A g(-1)) along with the excellent durability showing 85% capacitance retention over 4000 cycles at 0.5 A g(-1).
Keywords: lithium-ion capacitors; MXene; niobium molybdenum oxides; pseudocapacitive anode materials

Unveiling a promising active host material for sodium metal anodes through V2AlC max derivation - Wasnik, Kundan; Patrike, Apurva; Shelke, Manjusha V. (ACS Applied Energy Materials, 2024)
To address the issue of nonuniform sodium deposition, in this study, V2ZnC (named VZC), which is synthesized by substituting Zn for Al in V2AlC, is used as a host material to facilitate effective Na utilization. The key concept is to utilize Zn and its forms as an active site to trap Na, while the high mechanical strength of VZC can accommodate volume changes in the sodium metal anode during charging and discharging. VZC displayed regulated plating and stripping at a higher current and capacity of 8 mA cm-2 and 2 mAh cm(-2), respectively, with Coulombic efficiency close to 99.99%.
Keywords: electrodes; Nucleation; overpotential; sodium metal; XPS depth profiling

Exploring FeSe2 and porous carbon composite as a cost-effective host for Al3+ in aqueous Aluminum ion batteries - Mirzapure, Vinay; Patrike, Apurva; Shelke, V, Manjusha (Electrochimica Acta, 2025)
Aluminum is a high-energy-density material with low cost, making rechargeable aluminum ion batteries (AIBs) a attractive alternative to alkali metal ion batteries. However, the practical development of aqueous AIBs is hindered by limited electrode. Herein, we report FeSe2-decorated porous nitrogen and sulfur-doped carbon spheres (FSPNSCS) as a cathode material for aqueous AIBs, with an emphasis on the reaction kinetics and electrochemical performance. FSPNSCS is synthesized through a hydrothermal approach, confirmed by comprehensive characterizations using X-ray Diffraction for crystalline structure validation and Scanning Electron Microscopy for analyzing composite morphology. Electrochemical properties and kinetics are probed using cyclic voltammetry and galvanostatic charge-discharge tests. Ex-situ XRD reveals a notable peak shift towards higher 2 theta values during discharge, indicating lattice contraction due to Al3+ insertion. Sulfur and nitrogen doping impart elasticity to the lattice structure, enhancing stability during cycling. Ex-situ XPS confirms Al3+ storage and minimal oxide formation, as further supported by microscopic elemental mapping with HRTEM. The FSPNSCS cathode achieves a reversible capacity of 60 mAh g- 1 at a current density of 200 mA g- 1. The system exhibits outstanding cycling stability, retaining over 90 % of its capacity at 500 mA g- 1 over 1000 cycles, highlighting its potential to advance aqueous AIBs for sustainable energy storage.
Keywords: Aqueous aluminum ion battery; cathode material; Electrochemistry; Transition metal selenide